Absence of Atoh1 induced partially different cell fates of cochlear and vestibular sensory epithelial cells in mice. (2nd November 2018) - Zhang, Yongli; Tang, Qi; Xue, Ruoyan; Gao, Juanjuan; Yang, Hua; Gao, Zhiqiang; Lin, Gan
Abstract: Background： Atoh1, also named Math1, is essential for the development of inner ear hair cells. Many studies have confirmed that the absence of Atoh1 resulted in a total loss of inner ear hair cells, which indicates that Atoh1 plays very similar roles in the development of hair cells in the cochlea and vestibule. Objective： The aim of this study was to evaluate whether Atoh1 plays different roles in the cochlea and vestibule. Material and methods: We generated Atoh1-null mice by inbreeding Atoh1 cre/+ heterozygous mice and compared with the epithelial cell status of the cochlea and vestibule. Results: We found that no inner ear hair cells were detected in Atoh1-null mice. However, a different cell status was found in the mutant cochlea and vestibule on the last embryonic day (E18.5). In the Atoh1-null cochlea, the epithelial cells that should develop into hair cells were totally absent, while in the Atoh1-null vestibule, most of the epithelial cells that should develop into hair cells still survived. Conclusions: Our data indicate that Atoh1 may have similar but partially different functions in the development of hair cells in the cochlea and vestibule.